DINAMIKA RELASI SOSIAL PASANGAN LANJUT USIA EMPTY NEST DI DESA BOTUTONUO KECAMTAN KABILA BONE - Dewinta Rizky R. Hatu; Sahrain Bumulo; Muslima Musa (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
Social relationships play an important role in the lives of elderly empty-nest couples. Empty nest refers to a situation in which children have left the family home, leaving elderly couples to live together on their own. Under these circumstances, some parents often experience feelings of sadness, loneliness, and social isolation, which can have significant impacts on their lives, both emotionally and in terms of their social relationships.The purpose of this study is to understand the dynamics of social relations experienced by elderly couples in facing the empty nest condition. This research employed a qualitative method with a descriptive approach. Data were collected through field observations, in-depth interviews, and documentation. The informants consisted of elderly couples, village officials, and community members selected purposively based on their involvement and understanding of the social conditions of the elderly. Data analysis was carried out through data reduction, data presentation, and conclusion drawing and verification. The findings reveal that the empty nest condition brings emotional and social changes to elderly couples, including reduced family interaction and feelings of loneliness. Nevertheless, the elderly couples were able to adapt by engaging in daily activities such as gardening, trading, and participating in social activities within the community. Social relationships established through interactions with spouses, neighbors, and the surrounding community became important sources of social and emotional support in maintaining their daily lives.